A Global Review of Age-Specific and Overall Prevalence of Cervical Lesions. Issue 7 (1st October 2010) - Ting, Jie; Kruzikas, Denise T.; Smith, Jennifer S.
Abstract : Background: Overall and age-specific cervical cytological and histological abnormalities prevalence data across geographical regions, in conjunction with human papillomavirus vaccination status, will be important for the future evaluation of HPV prophylactic vaccine effectiveness. Methods: A systematic review was conducted to summarize worldwide data on the prevalence of high- and low-grade squamous intraepithelial lesions, and cervical intraepithelial neoplasia (CIN) 2/3 or 1. Results: More than 12, 400, 000 women were included in 103 studies. Most studies were from Europe and Middle East (40%) or North America (14%), 14% were from Asia, 17% from Central and South America, and 15% from Africa. Age-specific data were limited from Asia, Central and South America, and Africa. Screening techniques and study exclusion criteria varied, depending on region and population surveyed. Age trends of high-grade cervical lesions seemed to peak at a relatively younger age in North America (<30 years), compared with 25 to 40 years in Europe and Middle East, Africa, Asia, and Central and South America. Age patterns of low-grade lesions generally declined after a peak in the younger age groups (20-30 years). Age-specific CIN 1 and CIN 2/3 prevalence were lower compared with low- and high-grade squamous intraepithelial lesions from the same studies, respectively. Conclusions: Variation in the age patterns of high-grade lesions across regions is likely attributable to differences in age at screening initiation, frequency, coverage, and rates of follow-up of women with cervical abnormalities. Observed age patterns of low-grade lesions are generally consistent to those of human papillomavirus infection in women worldwide. Potential factors contributing to variations in the burden of cytological and histological abnormalities across studies include subjectivity in evaluating cytological slides and discrepancies in the processing, referral rates, and diagnostic interpretation of colposcopically directed biopsy.